O approche acadêmico sobre o rural brasileiro - Massuquetti, Angélica (História Econômica & História de Empresas, 2014)
This paper analyses the academic approach about the rural Brazil in the 1960s and 1970s. Based on a bibliography review, the results reveal that the subject rural became an issue of specific investigation to comprehend the singularity of the transformation process of the Brazilian society. The existence of a group of researchers and the production from this research confirms their interest, as well as the institutions that finance this research in the construction of a space of reflections on rural Brazil.